It's an aardvark-eat-turtle world - Danziger, Paula, 1944-2004. (New York : Delacorte Press, 1985)
At fourteen, Rosie, her mother, her best friend, and her best friend's father form a new family unit and find it takes a lot of work to make a family in a world of changing relationships.
Booklist.
Bulletin (Center for Children's books).
School Library Journal.
5.6
5.6
5-8.
Keywords: Divorce -- Fiction; Family life -- Fiction; Divorce -- Fiction; Family life -- Fiction